COMPARISON OF FIRST MORNING VOID URINE SPECIMEN FOR ALBUMIN TO CREATININE RATIO COMPARING WITH 24-HOUR URINARY ALBUMIN EXCRETION IN DETECTING MICROALBUMINURIA IN TYPE 2 DIABETICS: Albumin To Creatinine Ratio of Urine in Type 2 Diabetics - Ahmad, Fawad; Hussain, Aamir; Aziz, Omer Bin Abdul; Ahmed, Naveed (Pakistan Armed Forces Medical Journal, 2016)
Objectives: To determine the accuracy of first morning void urine specimen for Albumin to Creatinine Ratio (ACR) comparing with 24-hour urinary albumin excretion in detecting microalbuminuria in type 2 diabetics. Study Design: Cross Sectional study Place and Duration of Study: Military Hospital Rawalpindi, from Apr 2013 to Oct 2013. Patients and Methods: One hundred & twenty patients with type 2 Diabetes Mellitus (DM) fulfilling the inclusion criteria were included in study using consecutive non-probability sampling. A standard protocol was followed for specimen collection. Urine collection was started from the next day of admission. Results: Mean random plasma glucose level was 174.54 ± 33.06 mg/dL, mean HbA1c was 8.5 ± 1.32 %, mean urinary albumin 130.26 ± 47.25 mg/24 hour and mean ACR was 104.30 ± 51.56 mg/g. Area under ROC curve was 0.964 for microalbuminuria by ACR. Spearman’s rank-order coefficient (rs) was 0.696 for ACR and 24 hour albumin excretion. Conclusion: ACR in first morning void urine accurately detected early microalbuminuria in type 2 diabetics.